2002
DOI: 10.1590/s0034-70942002000400013
|View full text |Cite
|
Sign up to set email alerts
|

Anestesia na Pré-Eclâmpsia

Abstract: Justificativa e Objetivos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
(126 reference statements)
0
4
0
1
Order By: Relevance
“…Magnesium sulfate (MgSO 4 ) has been shown to have therapeutic effects in PE and reduces the release of acetylcholine in the 1 neuromuscular junction, which causes the muscles to relax, 16 increases the synthesis of prostacyclins, increases vasodilation by inhibiting angiotensin-converting enzyme 17 and improves sedation of the nervous system. 18 In addition, Dowling et al 19 found that administration of MgSO 4 inhibited LPS-induced excessive inflammation at the maternal-fetal interface.…”
mentioning
confidence: 99%
“…Magnesium sulfate (MgSO 4 ) has been shown to have therapeutic effects in PE and reduces the release of acetylcholine in the 1 neuromuscular junction, which causes the muscles to relax, 16 increases the synthesis of prostacyclins, increases vasodilation by inhibiting angiotensin-converting enzyme 17 and improves sedation of the nervous system. 18 In addition, Dowling et al 19 found that administration of MgSO 4 inhibited LPS-induced excessive inflammation at the maternal-fetal interface.…”
mentioning
confidence: 99%
“…Diversos autores encontraram aumento abrupto da FC nas primeiras quatro semanas de gestação, seguido por um aumento gradual, atingindo um platô de aproximadamente 15 batimentos por minuto acima dos valores da FCR no estado não gravídico (26,27,28). Esse aumento pode ser causado por ajustes vasculares e hemodinâmicos decorrentes da gestação (28).…”
Section: Discussionunclassified
“…Medicine has not elucidated completely the mechanism of action of magnesium sulfate used therapeutically 13 . Some of the following propositions have been developed over the years: a) Inhibition of the release of acetylcholine in the neuromuscular junction 9,14 leading to muscle relaxation, which has been known since the 1950s 3 . Hypermagnesemia decreases the sensitivity of the motor plate to acetylcholine and the amplitude of terminal end-plate potential 9 .…”
Section: Physiology and Pharmacologic Effetcsmentioning
confidence: 99%
“…It has been postulated that the anticonvulsant property of magnesium sulfate is due to the blockade of NMDA receptors 5,14 .…”
Section: Obstetric Applicationsmentioning
confidence: 99%